Penggunaan Serat Optik Sebagai Pemancar Cahaya Pada Pembuatan Cocktail Dress - Ariyana Damayanti; Irmatul Afizah; Rizka Puspa Sari; Sindy Aulia Putri (Garina, 2021)
The use of Fiber Optic as a light emitter in Cocktail Dress is expected to be a new innovation in the development of party fashion. The objectives of this study are: 1) To explain the process of making a cocktail dress using Fiber Optic as a light emitter. The method used in this research is the Research and Development (R & D) method. The R&D method is a research method that tests a product to produce the best product by conducting direct trials. In addition to using the method (R&D), it also uses the method of literature, documentation, and experiments. The experiment of making Cocktail Dress using Fiber Optic as a light emitter was carried out at the Laboratory of the Fashion Design Study Program of the Kartini Academy of Social Welfare, st. Sultan Agung, No. 77 Gajah Mungkur Village, Semarang City. The percentage of additional ingredients in making Cocktail Dress, namely: 3 meters Bridal Satin Fabric, 1meter Furing, 2 meters Trikod, 1 seed thread, zipper size 50 cm 1 item, zippers size 25 cm 1 item, Fiber Optic in amount of 0.75 mm-400 m. The results of this study indicate that the Fiber Optic Cocktail Dress has the characteristic that the resulted cocktail dress can shine with the light emitting from the Fiber Optic. Thus, it can be concluded that there is an opportunity for innovation from Cocktail Dress by adding Fiber Optic.